Statistical Modelling and Correlation of Membrane Distillation Data - Hamdoon, Azza (2014)
A Master of Science thesis in Chemical Engineering by Azza Hamdoon entitled, "Statistical Modelling and Correlation of Membrane Distillation Data," submitted in July 2014. Thesis advisor is Dr. Naif Darwish. Available are both soft and hard copies of the thesis.